Does the Learning Value of Individual Failure Experience Depend on Group Level Success? Insights from a University Technology Transfer Office - ZHENG, Yanfeng (Institutional Knowledge at Singapore Management University, 2013)
This study proposes that individual failure experience in organizations induces useful learning at the individual and group levels because it reveals valuable information and spurs actions. However, the value of individual failure experience depends on the level of group success experience. Specifically, group contemporary success experience and group congenital success experience will enhance the learning value of individual failure experience. Each type of higher level of group success experience provides useful experience pools (library effect), offers contrasts that are crucial for causal inferences (contrast effect), and motivates the focal individuals and the group to learn (motivation effect), albeit through distinct microprocesses. We test our theory with an event history analysis of the first licensing agreements for 778 lead patents granted to a major university technology transfer organization between 1971 and 1999, and find support for our theory. Our study presents an integrated model for organizational learning that involves internal failure and success across levels, and offers a framework for multilevel internal learning from experience.